2022
DOI: 10.1016/j.chb.2021.107060
|View full text |Cite
|
Sign up to set email alerts
|

Do I still like myself? Human-robot collaboration entails emotional consequences

Abstract: Investigating emotional processes has been vital for understanding human-human interaction. Specifically, emotional concepts of oneself and the interaction partner shape the interaction style and are associated with mental health and cognitive performance. Here, it is investigated whether these concepts are equally relevant in human-robot interaction (HRI). We measured emotional concepts before and after online collaboration with a robot described as (a) able, (b) unable to experience emotions, or (c) autonomo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In other words, if two CMs exhibit similar performances, it is likely beneficial to stick with one CM rather than to switch things up. Considerable CM perseveration, sometimes with participants who exhibited no single CM switchsometimes for more than 100 trials-was found with a variety of paradigms (Bourne et al, 2010;Scarampi & Gilbert, 2020;Weis & Herbert, 2022;Weis & Wiese, 2019b, 2019a.…”
Section: Is Self-chosen And/or Cued Perseveration On Specific Cms Ben...mentioning
confidence: 99%
“…In other words, if two CMs exhibit similar performances, it is likely beneficial to stick with one CM rather than to switch things up. Considerable CM perseveration, sometimes with participants who exhibited no single CM switchsometimes for more than 100 trials-was found with a variety of paradigms (Bourne et al, 2010;Scarampi & Gilbert, 2020;Weis & Herbert, 2022;Weis & Wiese, 2019b, 2019a.…”
Section: Is Self-chosen And/or Cued Perseveration On Specific Cms Ben...mentioning
confidence: 99%
“…Such bimodal strategy use has been found in situations with no prior experience with either strategy, which indicates some sort of reluctance to explore performance of the respective other strategy (Fig. 1 a; Weis & Herbert, 2022 ). However, even if participants had extensive experience only with an internal strategy, strong perseveration was found (Fig.…”
Section: ‬Perseveration: Problem Solvers Rarely MIX Internal and Exte...mentioning
confidence: 89%
“…Perseveration is reflected by bimodal distributions in the present figures. Data was obtained from joint arithmetic and social problem solving with a telepresent agent (a; Weis & Herbert, 2022 ), from solving alphanumeric problems with or without help from a computer (b; Weis & Wiese, 2019a ), from intention offloading with or without spatial manipulation on a computer screen (c–f; Scarampi & Gilbert, 2020 ), and from an object rotation task with mental rotation or manual computer-mediated rotation (g; Weis & Kunde, 2022 ). Dashed gray lines represent means with the p -value of one-sample t -tests testing against μ = 50% attached.…”
Section: Introductionmentioning
confidence: 99%
“…Group-wise, this leads to a bimodal distribution with peaks at low and high eCM use proportion or a unimodal distribution with peaks at low or high eCM use proportion (compare Figure 1). Such bimodal CM use distributions have been found in situations with no prior experience with neither eCM nor iCM (Figure 1a; Weis & Herbert, 2022), which illustrates some sort of indifference with respect to exploring the other CM's performance. However, even if participants had extensive experience only with an iCM, strong perseveration was found (Figure 1b; Weis & Wiese, 2019a).…”
mentioning
confidence: 82%
“…Such perseverations on one of both mechanisms are reflected by a bimodal distribution. In particular, data was obtained from joint arithmetic and social problem solving with a telepresent agent (a; Weis & Herbert, 2022), from solving alphanumeric problems with or without help from a computer (b; Weis & Wiese, 2019a), from intention offloading with or without spatial manipulation on a computer screen (c-f Scarampi & Gilbert, 2020), and from an object rotation task with mental or manual computer-mediated rotation (g; ` Weis & Kunde, 2022). Dashed gray lines represent means.…”
Section: Figurementioning
confidence: 99%